Fu’s Subcutaneous Needling Combined with Kinematic Acupuncture versus Electroacupuncture in the Treatment of Cervical Spondylotic Radiculopathy: A Randomized Controlled Trial [Letter] - Pan X; Liu Q (Journal of Pain Research, 2025)
Xiaofeng Pan, Qiang Liu The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of ChinaCorrespondence: Qiang Liu, The Third Affiliated Hospital of Zhejiang Chinese Medical University, No. 219 Moganshan Road, Hangzhou, Zhejiang, People’s Republic of China, Email 19981011@zcmu.edu.cn